Decision to deploy coronary reperfusion is not affected by the volume of ST-segment elevation myocardial infarction patients managed by prehospital emergency medical teams. (December 2019) - Lapostolle, Frédéric; Bataille, Sophie; Loyeau, Aurélie; Simon, Benoît; Laborne, François-Xavier; Dupas, François; Boche, Thévy; Lamhaut, Lionel; Pirès, Virginie; Lefort, Hugues; Mapouata, Mireille; Le Bail, Gaëlle; et al.
Abstract : Objective: Mortality in patients with ST-segment elevation myocardial infarction (STEMI) has been associated with the volume of activity of percutaneous coronary intervention (PCI) facilities. This observational study investigated whether the coronary reperfusion-decision rate is associated with the volume of activity in a prehospital emergency setting. Methods: Prospectively collected data for the period 2003–2013 were extracted from a regional registry of all STEMI patients handled by eight dispatch centers (SAMUs) in and around Paris [41 mobile ICU (MICUs)]. A possible association between volume of activity (number of STEMIs) and coronary reperfusion-decision rate, and subsidiarily between volume of activity and choice of technique (fibrinolysis vs. primary PCI), were investigated. Explanatory factors (patient age, sex, delay between pain onset and first medical contact, and access to a PCI facility) were analyzed in a multivariate analysis. Results: Overall, 18 162 patients; male/female 3.5/1; median age 62 (52–72) years were included in the analysis. The median number of STEMIs per MICU was 339 (IQ 220–508) and that of reperfusion-decisions was 94% (91–95). There was no association between the decision rate and the number of STEMIs ( P = 0.1). However, the decision rate was associated with age, sex, delay, and access to a PCI facility ( P < 0.0001) in a highly significant way. Fibrinolysis was a more frequent option for low-volume (remoter PCI facilities) than high-volume MICUs (30 vs. 16%). Conclusion: The decision of coronary reperfusion in a prehospital emergency setting depended on patient characteristics, delay between pain onset and first medical contact, and access to a PCI facility, but not on volume of activity. Promoting fibrinolysis use in underserved areas might help increase the reperfusion-decision rate.